Clusterin CSF levels in differential diagnosis of neurodegenerative disorders - Přikrylová Vranová, Hana; Hényková, Eva; Mareš, Jan; Kaiserová, Michaela; Menšíková, Kateřina; Vaštík, Miroslav; Hluštík, Petr; Zapletalová, Jana; Strnad, Miroslav; Stejskal, David; Kaňovský, Petr (Journal of the neurological sciences, 2016)
INTRODUCTION: Clusterin, a heterodimeric glycoprotein, is thought to be involved in many cellular functions, including cell-cell interaction, cell survival and apoptosis. In the brain, post-mortem analysis has found increased clusterin associated with the pathology of many other neurodegenerative diseases (ND) such as Parkinson's disease (PD), dementia with Lewy bodies (DLB), Alzheimer's disease (AD) and multiple system atrophy (MSA). In vivo cerebrospinal fluid (CSF) levels of clusterin in ND diseases may reflect differences in the pathology and thus aid in the differential diagnosis. METHODS: CSF levels of clusterin were assessed in 102 patients with clinical manifestations of neurodegenerative diseases (23 patients with PD, 18 with PDD, 15 with DLB, 18 with AD, 16 with PSP, 12 with MSA) and 21 subjects as a control group (CG). RESULTS: Significantly higher CSF clusterin levels were found in PD compared to CG (median 6884 vs. 4484; p=0.012), DLB (median 6884 vs. 4192; p=0.023), MSA (median 6884 vs. 3606; p=0.001) and PSP (median 6884 vs. 4193; p=0.014). Significantly higher CSF clusterin levels were found in PDD compared to CG (median 8617 vs. 4484; p=0.045), DLB (median 8617 vs. 4192; p=0.025) and MSA (median 8617 vs. 3606; p=0.004). CONCLUSION: The results of the presented "feasibility" study support the role of clusterin in PD/PDD pathogenesis. Clusterin CSF levels could serve as a potential marker for PDD and DLB differentiation.
Keywords: senioři; diferenciální diagnóza; tau Proteins; proteiny tau; senioři nad 80 let; Parkinson's disease; Middle Aged; mužské pohlaví; klusterin; Aged, 80 and over; ženské pohlaví; Humans; Neurodegeneration; biologické markery; Neurodegenerative Diseases; CSF; lidé středního věku; Diagnosis, Differential; neurodegenerativní nemoci; Biomarkers; Female; Aged; Alzheimer disease; Clusterin; lidé; Male